2023
DOI: 10.1371/journal.pcbi.1011529
|View full text |Cite
|
Sign up to set email alerts
|

Natural variability in bee brain size and symmetry revealed by micro-CT imaging and deep learning

Philipp D. Lösel,
Coline Monchanin,
Renaud Lebrun
et al.

Abstract: Analysing large numbers of brain samples can reveal minor, but statistically and biologically relevant variations in brain morphology that provide critical insights into animal behaviour, ecology and evolution. So far, however, such analyses have required extensive manual effort, which considerably limits the scope for comparative research. Here we used micro-CT imaging and deep learning to perform automated analyses of 3D image data from 187 honey bee and bumblebee brains. We revealed strong inter-individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Previous work on U-Net segmentation showed that the number and quality of training datasets are crucial to achieving high accuracy of segmentation. 24 , 25 Therefore, we have measured the accuracy of the ACSeg by computing Dice coefficients 26 , 27 for U-Net trained on various SXT tomograms. We trained the ACSeg on 5, 10, 20, 30, and 43 datasets, see Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous work on U-Net segmentation showed that the number and quality of training datasets are crucial to achieving high accuracy of segmentation. 24 , 25 Therefore, we have measured the accuracy of the ACSeg by computing Dice coefficients 26 , 27 for U-Net trained on various SXT tomograms. We trained the ACSeg on 5, 10, 20, 30, and 43 datasets, see Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Third, the rendering software and protocols should further be developed particularly to shorten the arduous and still largely manual segmentation of target structures. Rather promising attempts have lately been made to cut the manual segmentation time from several hours to a few minutes using a deep learning-based fully automated segmentation of micro-CT images from ant (Toulkeridou et al, 2023) and bee (Lösel et al, 2023) brains. To take the automation a step further, an entire automatic rendering process from the scan to a standardised set of images should be available at least for certain diagnostic structures mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…To train our models in Biomedisa, we used a stochastic gradient descent with a learning rate of 0.01, a decay of 1 × 10 -6 , momentum of 0.9, and Nesterov momentum enabled. A stride size of 32 and a batch size of 24 samples per epoch were used alongside an automated cropping feature, which has been demonstrated to enhance accuracy [18]. The training of each network was performed on a Tesla V100S-PCIE-32GB graphics card with 30989 MB of available memory.…”
Section: Methodsmentioning
confidence: 99%